Comparison of PWM Techniques for a three level Modular Multilevel Inverter. (June 2017) - Harin, M. Mohan; Vanitha, V.; Jayakumar, M.
Abstract: Modular multilevel converter (MMC) is a kind of multilevel inverter topology suitable for HVDC and medium voltage applications. These types of converters are designed inorder to mitigate the drawbacks of conventional multilevel inverters like the difficulty of capacitor voltage balancing during higher level of operation, the need for output filters and interfacing transformer. The chopper cell configuration or half bridge cell is the simplest submodule configuration of MMC. In this paper, different Carrier based pulse width modulation techniques for chopper cell based MMC are compared for a lagging power factor load. Simulation analysis has been done using MATLAB/Simulink and the results are verified.